Monotonic properties of Kneser solutions of second order linear differential equations with delayed argument - Blanka Baculíková (Opuscula Mathematica)
In this paper new monotonic properties of nonoscillatory solutions for second order linear functional differential equations with delayed argument \[y{''}(t)=p(t)y(\tau(t))\] have been established. New properties are used to introduce criteria for elimination of bounded nonoscillatory solutions for studied equations.